Differences of methanogenesis between mesophilic and thermophilic in situ biogas-upgrading systems by hydrogen addition. (1st November 2019) - Zhu, Xianpu; Chen, Liumeng; Chen, Yichao; Cao, Qin; Liu, Xiaofeng; Li, Dong
Abstract: To investigate the differences in microbial community structure between mesophilic and thermophilic in situ biogas-upgrading systems by H2 addition, two reactors (35 °C and 55 °C) were run for four stages according to different H2 addition rates (H2 /CO2 of 0:1, 1:1, and 4:1) and mixing mode (intermittent and continuous). 16S rRNA gene-sequencing technology was applied to analyze microbial community structure. The results showed that the temperature is a crucial factor in impacting succession of microbial community structure and the H2 utilization pathway. For mesophilic digestion, most of added H2 was consumed indirectly by the combination of homoacetogens and strict aceticlastic methanogens. In the thermophilic system, most of added H2 may be used for microbial cell growth, and part of H2 was utilized directly by strict hydrogenotrophic methanogens and facultative aceticlastic methanogens. Continuous stirring was harmful to the stabilization of mesophilic system, but not to the thermophilic one.